Reducing the Environmental Impact of Cork Waste by Improving Natural Asphalt as Water Proofing Material - Bashar Abdulazeez Mahmood1, Majid Ahmed Mohaisen 2 , Adil Hasan Mahmood3 , Saadoon O. Eyada4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
This research is concern with two principles, a) the environmental pollution which is the global problem b)the economic benefits as a result of reusing of waste material such as corks to produce new reusable materiallike Modified-Asphalt. In this research cork has melted by benzene and mixed with Hit Natural Asphalt toget good paste with weight percentages of 0%, 10%, 20%. The properties of Modified –Asphalt have beenstudied after and before adding coke. The results revealed that adding coke by 29% can make the Modified–Asphalt meets the international specifications (ASTM D312) and Iraqi specifications (88-1196) as a Waterproofing material.